Severe acute respiratory failure (SARF) secondary to concurrent pulmonary‐only anti‐GBM syndrome and thrombo‐embolic disease. Issue 1 (23rd January 2017) - Charlton, Matthew; Bell, Ricky; Yusuff, Hakeem; Vaja, Rakesh
Summary: We report the case of a 20‐year‐old male patient presenting to the Emergency Department with severe type 1 respiratory failure due to diffuse alveolar haemorrhage secondary to pulmonary‐only anti‐glomerular basement membrane (anti‐GBM) disease, a rare presentation of this reno‐pulmonary syndrome. The patient had developed multiple pulmonary venous emboli and an intracerebral arterial thrombus. There are limited reports of pulmonary emboli coinciding with anti‐GBM disease and no other reports of concomitant arterial thrombus. We describe the presentation and consider the management of this rare, serious cause of hypoxaemia and the possible role of extra‐corporeal membrane oxygenation in this patient group. We review the pathophysiology of anti‐GBM disease and the reported cases of accompanying venous or arterial thrombo‐emboli in related conditions.